Nansen i norsk polartradisjon - Harald Dag Jølle (Nordlit: Tidsskrift i litteratur og kultur, 2014)
Fridtjof Nansen’s expeditions introduced polar exploration in Norway. And his stories from the North formed our image of the Arctic. For later generations of Norwegian explorers Nansen surely has been a great inspiration. Also within polar science Nansen serves as a hero. The article asks to what extent Nansen shared the general political view on Norwegian polar imperialism in the interwar period. That reminds us simultaneously that not all of today's political polar ambitions necessarily are in accordance with Nansen's vision for Arctic research.